Mirar animales: la caminata por el zoológico en Desubicados de María Sonia Cristoff y Paraísos de Iosi Havilio. - OLIVER, MARÍA PAZ (Revista de Estudios Hispánicos, 2018)
This article analyzes the representation of walking in the zoo in two recent Argentine novels: María Sonia Cristoff's Desubicados and Iosi Havilio's Paraísos. As a place of control and domination, the zoo is based on an image of the exotic and the illusion of natural habitats. The routine and marginalization of the animals create an emotional relation with the protagonists, two women who see the zoo as a refuge and a place to escape from their everyday life. Walking in the zoo is an experience that encourages a reflection on its anachronism and artificial condition, which is also related to the space of the city, its transformations, and the ways to explore the urban space. Thus walking has the power to appropriate the space as it creates a nostalgic and psychogeographic map of Buenos Aires.